Gamma Ray Attenuation in Hevea Latex and its Application to DRC Measurement - Saion, Elias; Sin, Deou Seang; Abdul Sulaiman, Zainal; Ikhsan, Sabirin; Wagiran, Husin (1986)
This paper reports the measurement of the total solid content (TSC) of fresh Hevea latex by the gamma ray attenuation technique. The component ratios of the total volume of water and solid material in multiphase system of latex were determined by the measurement of attenuation coefficient of latex with high energy resolution Si(Li) detector at low gamma ray energies. The result was compared against the Standard Laboratory Method and the correlation coefficient was found to be 0.998. Based on the behavior that the interaction of gamma ray with matter at a given energy depends upon the atomic number of the material, the present technique may be able .to detect adulterants in the latex, but investigations are needed to verify this.